Report on implementation of the Landscape Assessment of Financial Flows (LAFF) in Gunung Tarak Landscape, Indonesia - Rossanda, D.; Pamerneckyte, G.; Koesoetjahjo, I.; Louman, Bastian (2020)
In 2018 to support collaborative landscape initiatives, Tropenbos International and EcoAgriculture Partners partnered to develop the Landscape Assessment of Financial Flows (LAFF) methodology. This practical two–phase approach helps stakeholders identify local sources of finance for new investment ideas, [to] find the current financial flows that are most in need of transformation, and better understand the elements of a landscape’s financial context that require support. This report summarizes the results of a pilot application of both phases of LAFF in the Gunung Tarak Landscape in Indonesia from September 2018 until July 2019 and discusses the possible implications for the design of an integrated landscape finance strategy in that landscape.